Identification of microbiological factors associated with periodontal health disparities - Wang, Bing-Yan; Cao, Aize; Ho, Meng-Hsuan; Wilus, Derek; Sheng, Sally; Meng, Hsiu-Wan; Guerra, Elissa; Hong, Jianming; Xie, Hua (Frontiers in Cellular and Infection Microbiology, 2023)
The present study aimed at identifying risk factors associated with periodontitis development and periodontal health disparities with emphasis on differential oral microbiota. The prevalence of periodontitis is recently rising dentate adults in the US, which presents a challenge to oral health and overall health. The risk of developing periodontitis is higher in African Americans (AAs), and Hispanic Americans (HAs) than in Caucasian Americans (CAs). To identify potentially microbiological determinations of periodontal health disparities, we examined the distribution of several potentially beneficial and pathogenic bacteria in the oral cavities of CA, AA, and HA study participants. We collected dental plaque samples from 340 individuals with intact periodontium prior to any dental treatment and quantitated oral bacteria using qPCR and obtained the medical and dental histories of these individuals retrospectively from axiUm. Data were analyzed statistically using SAS 9.4, IBM SPSS version 28, and R/RStudio version 4.1.2. We discovered that: 1) neighborhood medium incomes were significantly higher in the CA participants than the AA and the HA participants; 2) levels of bleeding on probing (BOP) were higher in the AAs than in the CAs and HAs; 3) Porphyromonas gingivalis levels were higher in the HAs compared to that in the CAs; 4) most P. gingivalis detected in the AAs were the fimA genotype II strain that was significantly associated with higher BOP indexes along with the fimA type IV strain. Our results suggest that socioeconomic disadvantages, higher level of P. gingivalis, and specific types of P. gingivalis fimbriae, particularly type II FimA, contribute to risks for development of periodontitis and periodontal health disparities.